2019
DOI: 10.3390/molecules24050882
|View full text |Cite
|
Sign up to set email alerts
|

Alternative Ultrasound-Assisted Method for the Extraction of the Bioactive Compounds Present in Myrtle (Myrtus communis L.)

Abstract: The bioactive compounds in myrtle berries, such as phenolic compounds and anthocyanins, have shown a potentially positive effect on human health. Efficient extraction methods are to be used to obtain maximum amounts of such beneficial compounds from myrtle. For that reason, this study evaluates the effectiveness of a rapid ultrasound-assisted method (UAE) to extract anthocyanins and phenolic compounds from myrtle berries. The influence of solvent composition, as well as pH, temperature, ultrasound amplitude, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
34
0
1

Year Published

2019
2019
2025
2025

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 37 publications
(42 citation statements)
references
References 57 publications
4
34
0
1
Order By: Relevance
“…This technique has many advantages, since it decreases extraction and processing times, reduces energy and solvent consumption, and improves extraction performance. In addition, it is an easy, flexible, versatile and low-cost technique [15,16], as it has already been proven with other fruits such as grapes [17] or myrtle berries [18].…”
Section: Introductionmentioning
confidence: 99%
“…This technique has many advantages, since it decreases extraction and processing times, reduces energy and solvent consumption, and improves extraction performance. In addition, it is an easy, flexible, versatile and low-cost technique [15,16], as it has already been proven with other fruits such as grapes [17] or myrtle berries [18].…”
Section: Introductionmentioning
confidence: 99%
“…The variables chosen for the optimization were: Solvent of extraction (25%-75% methanol in H 2 O), the extraction temperature (10-70 • C), the amplitude (30%-70% of the maximum amplitude −200 W), the cycle (0.2-0.7 s), the pH of the extraction solvent (2-7), and the amount of sample (g):volume of the extraction solvent (mL) ratio (0.5:10-0.5:20). Methanol was used as the extraction solvent, due to the very good extractant qualities for this type of compound, such as its small size (easy penetration capacity), low density, and polarity related to the polarity of the studied compounds [38,41,42,44].…”
Section: Extraction Proceduresmentioning
confidence: 99%
“…Furthermore, the extraction efficiency can be increased by using a greater range of temperatures, since the number of bubbles formed in the cavitation phenomenon increases [39,40]. UAE has been earlier applied to extract bioactive compounds from different matrices, such as myrtle, [41], black chokeberry [42], perlette grapes [43], sesame [44], etc. Additionally, this technique is easy to use and cheaper than other extraction techniques.…”
Section: Introductionmentioning
confidence: 99%
“…Phenolic constituents are generally associated with health-promoting properties and the prevention of several degenerative diseases. Some studies have demonstrated their relation to antioxidant and anticancer properties in general [33][34][35]. The main phenolic compounds that could be found in açai are protocatechuic acid, epicatechin, benzoic acid, caffeic acid, chlorogenic acid, ferulic acid, syringic acid, vanillic acid, p-coumaric acid, orientin, isoorientin, vitexin, and procyanidins, amongst others [10,24].…”
Section: Introductionmentioning
confidence: 99%